Optimization of GPC3-specific chimeric antigen receptor structure and its effect on killing hepatocellular carcinoma cells. Issue 1 (1st January 2021) - Zhao, Jianfeng; Lin, Lijuan; Luo, Yihua; Cai, Qinghe; Jiang, Xiaojie; Liao, Changxi; Wei, Huimin
ABSTRACT: To investigate the effect of optimized GPC3-specific chimeric antigen receptor (GPC3-CAR) structure on killing hepatocellular carcinoma (HCC) cells. We constructed three lentiviral expression vectors with different CAR structures by genetic engineering and molecular cloning techniques. These three CAR structures shared the same intracellular signaling region consisting of 4–1BB and CD3ζ, but had different hinge and transmembrane regions. Specifically, GPC3-O4-CAR contained an optimized CD8α hinge region and a 4–1BB transmembrane domain; GPC3-CD8-CAR contained an optimized CD8α hinge region and a CD8α transmembrane domain; and GPC3-ori-CAR contained an original CD8α hinge region and a 4–1BB transmembrane domain. With similar transfection efficiency, it was observed by fluorescence microscopy that GPC3-O4-CAR expression on the surface of 293 T cells was much higher than those of the other two. Cytotoxicity experiments showed that T or NK cells with GPC3-O4-CAR structure were more lethal and could secrete more IFN-γ than the other two. In conclusion, GPC3-O4-CAR can be efficiently and stably expressed on the cell surface. Moreover, both the killing effect of transduced T and NK cells on GPC3-positive HCC cells and release of IFN-γ are increased. Graphical Abstract: uf0001